2017
DOI: 10.1186/s12911-017-0537-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel data-driven workflow combining literature and electronic health records to estimate comorbidities burden for a specific disease: a case study on autoimmune comorbidities in patients with celiac disease

Abstract: BackgroundData collected in EHRs have been widely used to identifying specific conditions; however there is still a need for methods to define comorbidities and sources to identify comorbidities burden. We propose an approach to assess comorbidities burden for a specific disease using the literature and EHR data sources in the case of autoimmune diseases in celiac disease (CD).MethodsWe generated a restricted set of comorbidities using the literature (via the MeSH® co-occurrence file). We extracted the 15 most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Prior work shows that some important phenotypic characteristics can only be inferred from text reports (Shivade et al, 2014). For example, Escudié et al (2017) observed that 92.5% of information regarding autoimmune thyroiditis is only presented in text. Despite the potential valuable information in medical notes, prior work also points out the redundancy in EHRs.…”
Section: Related Workmentioning
confidence: 99%
“…Prior work shows that some important phenotypic characteristics can only be inferred from text reports (Shivade et al, 2014). For example, Escudié et al (2017) observed that 92.5% of information regarding autoimmune thyroiditis is only presented in text. Despite the potential valuable information in medical notes, prior work also points out the redundancy in EHRs.…”
Section: Related Workmentioning
confidence: 99%
“…Our study expands beyond existing literature by exploring DX code assignment beyond accuracy 1,22,47 and shifts the view of static clinical data as raw analysis material to data as the product of clinical workflows. Our findings are congruent with the existing literature [15][16][17]36 but also unlock new dimensions of oncologic data quality assurance.…”
Section: Resultsmentioning
confidence: 93%
“…This work contributes to the growing field of co-occurence based phenotype network study. Whilst many previous studies have investigated comorbidity alone, often using electronic health records and billing codes [ 15 , 53 56 ], fewer approaches have looked at genes shared between phenotypes [ 22 , 23 , 57 , 58 ]. Moreover, most of these studies have used disease/phenotype-gene mapping taken from databases, rather than using patient data directly.…”
Section: Discussionmentioning
confidence: 99%